PENGARUH PENGUASAAN MUFRODAT TERHADAP KEMAMPUAN MENULIS PADA PEMBELAJARAN BAHASA ARAB - Mochamad Afroni; Fauziah (Bashrah, 2025)
The mastery of the vocabulary of MI Permata Sunnah students is not yet optimal, because there are no indicators related to students' optimal mastery of vocabulary which includes active (listening-writing) passive receptive (listening-reading) vocabulary mastery. This study uses a quantitative method. For data collection using observation, interview, questionnaire and documentation methods, to determine the mastery of vocabulary on the writing skills of grade 4 students at Permata Sunnah Elementary School, Sidrap Regency. With the following research results: 1. The mastery of the vocabulary of MI Permata Sunnah students is not always optimal. Because there are no indicators related to the mastery of students' vocabulary that is developing optimally, which includes active vocabulary mastery (listening-writing) passive receptive (listening to reading). 2. The ability to write Arabic at MI Permata Sunnah students is quite good, because the teachers who teach are already very expert in the field of Arabic, so that students get maximum results. 3. The influence of mastery of the MI Permata Sunnah vocabulary will be interrelated with supporting in determining someone in developing Arabic writing skills, the position of the vocabulary has the most important role in the ability to write Arabic.